Pemanfaatan Sensor Pada Smartphone Android Untuk Rekomendasi Pembibitan Tanaman - Sony Heri Maulana; Eko Budi Setiawan (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
Ornamental plants are plants that can meet psychological needs, improve the environment, and have the value of satisfaction as a hobby. Functionally, ornamental plants can help renew oxygen in the air, helping to reduce gas pollutants and noise. Then it takes an android application that can provide recommendations for ornamental plants using mobile sensor technology. The sensors used are humidity sensor, temperature sensor, and ambient light sensor, open wether map where the three sensors detect the level of humidity, temperature, and light intensity in the user environment then the application will recommend plants that are suitable for the environment, for Openweather as a sensor replacement if not supported by the sensor